The Role of Gender Dynamics in the Relationship between Parental Maltreatment and Juvenile Theft in South Korea - Han, Yoonsun (2014)
Juvenile theft is the leading crime among adolescents in Korea and is a serious social concern. The present study is an examination of youth theft in the framework of general strain theory, which asserts that criminal behavior occurs as a response to various strains, such as parental abuse and neglect. To test the role of parent-youth gender dynamics in the relationship between parental strain and youth theft, the current study analyzed a community-based sample of youth offenders and non-offenders in Korea (N = 374) using multivariate logistic regression models with interaction terms. Paternal physical abuse and maternal neglect predicted greater youth involvement in theft behavior. Regarding parent-youth gender dynamics, there was no difference in the role of maternal or paternal maltreatment in predicting theft behavior in sons or daughters. The exception was fathers' neglect, in which daughters showed higher odds of theft engagement than did sons who experienced even greater paternal neglect. The findings underscored the distinct and detrimental role of parental maltreatment in adolescent theft. The results supported the need to reach out to parents in consideration of the youth's gender and provided important implications for guiding current social services in preventing juvenile theft in Korea